2018
DOI: 10.1016/j.jneuroling.2017.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Working memory treatment in aphasia: A theoretical and quantitative review

Abstract: A B S T R A C TWorking memory (WM) is a frequent and long-lasting deficit in patients with aphasia. Progress has been made in our understanding of the nature of WM impairment, by considering deficits at the level of maintenance of item and serial order information (short-term memory), deficits at the level of attentional control, and their complex interactions with language impairment. However, WM treatment studies in aphasic patients remain scarce. This theoretical and quantitative review of 15 single-case tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 92 publications
0
7
0
2
Order By: Relevance
“…The goal is not just to say what representations are impaired, but the nature of the impairment. This motivates an emphasis on cognitive abilities such as short-term memory (Saffran, 1990; Martin et al, 1994; Martin and Saffran, 1997), working memory (Wright and Shisler, 2005; Wright and Fergadiotis, 2012; Majerus, 2018), attention (Tseng et al, 1993; Murray et al, 1998; Hula and McNeil, 2008; Martin and Allen, 2012) and executive functions (Miyake et al, 2000; Martin and Allen, 2008; Allen et al, 2012). Thus, a theory of aphasia is evolving to encompass both representational and processing components.…”
Section: Resultsmentioning
confidence: 99%
“…The goal is not just to say what representations are impaired, but the nature of the impairment. This motivates an emphasis on cognitive abilities such as short-term memory (Saffran, 1990; Martin et al, 1994; Martin and Saffran, 1997), working memory (Wright and Shisler, 2005; Wright and Fergadiotis, 2012; Majerus, 2018), attention (Tseng et al, 1993; Murray et al, 1998; Hula and McNeil, 2008; Martin and Allen, 2012) and executive functions (Miyake et al, 2000; Martin and Allen, 2008; Allen et al, 2012). Thus, a theory of aphasia is evolving to encompass both representational and processing components.…”
Section: Resultsmentioning
confidence: 99%
“…Low internal and external validity makes it difficult to draw conclusions about the beneficial effects of STM/WM treatments in stroke aphasia. A recent, related review by Majerus (2017) described the efficacy of STM/WM treatments using calculations of effect sizes for individual participants (Beeson & Robey, 2006) and a Bayesian one-sample t test to calculate overall effects across participants in the included studies. The conclusion drawn by Majerus, who acknowledged issues about specificity of treatment and content validity, was that STM/WM treatment studies appear to show satisfactory levels of efficacy.…”
Section: Methodological Qualitymentioning
confidence: 99%
“…To date, little is known about the evidence-base of STM/WM treatments in aphasia. While there have been recent narrative reviews (Majerus, 2017;Minkina, Rosenberg, Kalinyak-Fliszar, & Martin, 2017;Murray, 2012;Salis et al, 2015), to our knowledge, systematic reviews of STM/WM treatment studies in stroke aphasia have not been reported previously. Also, previous reviews have not focused on broad and systematic evaluation of the methodological quality of STM/WM treatments, which is the main focus of the present systematic review.…”
Section: Motivation Of the Present Studymentioning
confidence: 98%
See 1 more Smart Citation
“…Therefore, aphasiologists developed different training methods to enhance deficient non-language cognitive functions. Several studies have reported beneficial effects of working memory and attention trainings on sentence comprehension in individuals with aphasia (Javadipour et al, 2018;Majerus, 2018;Zakarias et al, 2018). In our Laboratory of Neuropsychology, Nencki Institute of Experimental Biology PAS, the innovative therapeutic tool Dr. Neuronowski® based on TIP was developed.…”
Section: Introductionmentioning
confidence: 99%